Analysis of suitability and carrying capacity of baronang fish (Siganus sp) cultivation in coastal waters of Maros Regency - Muhammad Haritza Laitte; Jaya Jaya; Febri Febri (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Siganus sp is one of the leading commodities that have high economic value. Until now, the market demand for Siganus sp continues to increase so that the prospect of its cultivation is very promising. The problem that arises specifically for fishermen in the coastal sub-district of Maros Regency is that there is no data and knowledge about suitable locations for the cultivation of Siganus sp. This study aims to determine the area that is suitable for cultivation of Siganus sp in the coastal district of Maros Regency. Data collection techniques were carried out by literature studies and direct field observations by taking coordinates and measuring oceanographic parameters (temperature, salinity, pH, brightness, dissolved oxygen, depth, current velocity). Water quality data were analyzed by weighting, overlaying and layout using GIS analysis. This research was conducted in the waters of the coastal sub-district of Maros Regency in January-August 2021. The results showed that the location of the suitability of Siganus sp aquaculture waters in the coastal sub-district of Maros Regency obtained suitable waters (S) for the development of Siganus sp cultivation covering an area of 630.36 ha and waters that are not suitable (N) for the development of cultivation Siganus sp covering an area of 681.2 ha.